Три медведя: [для детей дошкольного возраста] / художник В. А. Жигарев - Жигарев В. А. (Сказки, 2019)
Экземпляры: ДБ (20200528) / Инвентарный номер: 52088 / Цена: 50.00 / Сис.шифр: Д / Авт.знак: Т 67 / ГРНТИ: 17.71 / ББК: 82.3(2)